1994
DOI: 10.1007/bf02768019
|View full text |Cite
|
Sign up to set email alerts
|

Testicular seminoma: 20-year experience at the Northern Israel Oncology Center (1968–1988)

Abstract: Eighty-four patients with testicular seminoma were treated at the Northern Israel Oncology Center during the years 1968-1988. Using the staging classification of Hussey, 69 patients (82%) had Stage I, eight (10%) had Stage IIA, four (5%) had Stage IIB, one (1%) had Stage IIIA, and two (2%) had Stage IIIB disease. Sixty-nine patients (82%) had classic pure seminoma, nine (11%) had anaplastic seminoma and six (7%) had spermatocytic seminoma. Seventy-four patients (88%) underwent high inguinal orchiectomy and ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another important complication related to irradiation is a cardiac disease [15,22]. Gastrointestinal symptoms/peptic ulceration, impaired fertility and sexual problems are also associated with radiotherapy [23][24][25][26]. The results of M.D.…”
Section: Discussionmentioning
confidence: 97%
“…Another important complication related to irradiation is a cardiac disease [15,22]. Gastrointestinal symptoms/peptic ulceration, impaired fertility and sexual problems are also associated with radiotherapy [23][24][25][26]. The results of M.D.…”
Section: Discussionmentioning
confidence: 97%
“…All patients were referred after orchiectomy and full pretreatment evaluation, including hematological and chemistry analyses, chest radiograph and bipedal lymphangiography; since 1980, tumor marker assessment (serum ␤-human choriogonadotrophin and ␣-fetoprotein) and computerized tomography of the upper/lower abdomen and lungs have become routine. Radiation techniques have been described in detail elsewhere [1].…”
Section: Methodsmentioning
confidence: 99%
“…Early testicular seminoma is a very radiosensitive tumor with survival rates of 90-98% with no apparent severe acute or late side effects [1]. Although extensive literature suggests increasing cancer induction following exposure to low-and moderate-dose radiation therapy, the real risk has been difficult to document.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation for seminoma has also been associated with peptic ulcer disease and infertility. Reported rates of peptic ulcers have ranged from 0-16% [4,39,40,41,42,43,44]. The MRC TE10 phase III study comparing para-aortic to dog-leg radiation fields collected toxicity data systematically and reported that, with a median follow-up of 4.5 years, 33 of 478 men (7%) were diagnosed with a peptic ulcer [42].…”
Section: Radiation Therapy and The Risk Of Secondary Malignancies Andmentioning
confidence: 99%